2022
DOI: 10.1136/thoraxjnl-2021-217858
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes following emergency admission to hospital for COVID-19 compared with influenza: retrospective cohort study

Abstract: BackgroundWe examine differences in posthospitalisation outcomes, and health system resource use, for patients hospitalised with COVID-19 during the UK’s first pandemic wave in 2020, and influenza during 2018 and 2019.MethodsThis retrospective cohort study used routinely collected primary and secondary care data. Outcomes, measured for 90 days follow-up after discharge were length of stay in hospital, mortality, emergency readmission and primary care activity.ResultsThe study included 5132 patients admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
0
0
Order By: Relevance
“…Interestingly, SARI patients positive for influenza were significantly younger than those positive for SARS-CoV-2. Similar observations have been reported from other studies carried out in the United Kingdom [ 34 ] and Brazil [ 35 ]. In Italy, older age is among the most important predictors of both SIV [ 36 ] and COVID-19 [ 37 ] vaccination uptake.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, SARI patients positive for influenza were significantly younger than those positive for SARS-CoV-2. Similar observations have been reported from other studies carried out in the United Kingdom [ 34 ] and Brazil [ 35 ]. In Italy, older age is among the most important predictors of both SIV [ 36 ] and COVID-19 [ 37 ] vaccination uptake.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous research, we observed a significant association between receiving follow-up care at the primary care level shortly after respiratory infection hospitalisation and improved health outcomes. 32 This association can plausibly be attributed to several important pathways. First, timely primary care follow-up facilitates the monitoring and management of symptoms after respiratory infection hospitalisation, leading to symptoms alleviation and reducing the risk of further development of complications.…”
Section: Discussionmentioning
confidence: 99%